UPAYA PENINGKATAN HASIL BELAJAR IPAS MELALUI MODEL PBL DENGAN PENDEKATAN SAINTIFIK PADA SISWA KELAS 5 DI SDN NGIPIK KAB TEMANGGUNG - Eksa Dewi Wulan Sari; Daimul Hasanah; Heri Maria Zulfiati; Feri Lingga Nugraha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve science and science learning outcomes for grade 5 students at SDN Ngipik through a PBL learning model with a scientific approach. This research uses the classroom action research (PTK) method which consists of two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. The instruments used were pretest and posttest questions. The sample used in this research was 16 grade 5 students at SDN Ngipik. Based on the research results and the results of the discussion, several conclusions can be drawn, namely the use of the Problem Based Learning model with a scientific approach improves student learning outcomes in magnetism, electricity and technology for life, the use of the Problem Based Learning model can help make it easier for students to remember the learning material, because directly to the problem, the use of the Problem Based Learning model can generate activity, motivation and creativity, students in learning, and the class atmosphere becomes enjoyable.